2023
DOI: 10.1007/s11154-023-09801-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards precision medicine in bariatric surgery prescription

Abstract: Obesity is a complex, multifactorial and chronic disease. Bariatric surgery is a safe and effective treatment intervention for obesity and obesity-related diseases. However, weight loss after surgery can be highly heterogeneous and is not entirely predictable, particularly in the long-term after intervention. In this review, we present and discuss the available data on patient-related and procedure-related factors that were previously appointed as putative predictors of bariatric surgery outcomes. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 191 publications
0
4
0
Order By: Relevance
“… 40 However, the diabetic remission mechanism is attributed to several factors, such as gastrointestinal hormones, patient adherence and compliance with treatment, and patient lifestyle. 41 Gloy et al found that bariatric surgery had a major impact on diabetic improvement, HDL level, obesity, metabolic syndrome, and quality of life compared with drug medications. 42 Among metabolic surgeries, RYGB was superior to other types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 40 However, the diabetic remission mechanism is attributed to several factors, such as gastrointestinal hormones, patient adherence and compliance with treatment, and patient lifestyle. 41 Gloy et al found that bariatric surgery had a major impact on diabetic improvement, HDL level, obesity, metabolic syndrome, and quality of life compared with drug medications. 42 Among metabolic surgeries, RYGB was superior to other types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The weight loss efficacy of bariatric metabolic surgery is known to be influenced by a variety of pre-operative factors. Several patient characteristics were identified as being determinants of weight loss and obesity-associated medical problem remission after bariatric metabolic surgery, among these diabetes is one of the most impactful [ 1 , 3 ]. Additionally, previous reports also suggest that patients with an eGFR under 30 mL/min/1.73m 2 tend to have worse weight loss outcomes after bariatric surgery [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous reports also suggest that patients with an eGFR under 30 mL/min/1.73m 2 tend to have worse weight loss outcomes after bariatric surgery [ 15 , 18 ]. However, the available evidence is derived from studies that presented some limitations, namely, the concomitant presence of dysglycemia, which could have impacted on data interpretation [ 1 , 3 ]. The aim of this study was to investigate whether bariatric metabolic surgery weight loss is influenced by creatinine clearance rate, eGFR, proteinuria, or albuminuria, in patients without the concomitant presence of dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation